Determining Green Purchase Intention: The Role of Perceived Green Value, Green Trust, and Attitude Toward Green Products - Rimiyati, Hasnah; Wardana, Ilham Kusuma (Indonesian Journal of Advanced Research, 2026)
This research analyzes the link between green perceived value and purchase intention within the context of sustainable consumption, specifically investigating the dual mediating roles played by green trust and attitudes toward green products. This analysis focuses on consumers of The Body Shop within the Special Region of Yogyakarta. Adopting a quantitative research design, this study employed a survey method involving the distribution of questionnaires to 150 respondents, who were recruited through a purposive sampling technique. Respondents were consumers who understood that the research object was an environmentally friendly product, had purchase intentions, and were at least 17 years old. To test the proposed conceptual model, this study utilized Partial Least Squares-Structural Equation Modeling (PLS-SEM), with the analysis performed using SmartPLS software. The data confirms that green perceived value has a robust positive impact on trust, attitude, and purchase intention within the context of environmentally friendly products. Furthermore, both green trust and product attitudes significantly enhance purchase intentions. Mediation tests further confirm that these two variables serve as critical pathways through which green perceived value affects consumer intentions. This study confirms that green value perception is essential for fostering trust and positive attitudes, which are pivotal in translating consumer interest into actual green purchase intent. This study contributes by developing a model that positions attitude toward green products as an alternative mediator, thereby enriching our understanding of the psychological mechanisms influencing the purchase behavior of green products.